2007 IEEE International Conference on Communications 2007
DOI: 10.1109/icc.2007.49
|View full text |Cite
|
Sign up to set email alerts
|

A TCP Connection Establishment Filter: Symmetric Connection Detection

Abstract: Abstract-Network measurement at 10+Gbps speeds imposes many restrictions on the resource consumption of the measurement application, making any filtering of input data highly desirable. Symmetric Connection Detection (SCD) is a method of filtering TCP sessions, passing only those sessions which become fully established. SCD can benefit network monitoring applications that are only interested fully established TCP connections by reducing processing requirements. Incomplete connection attempts, such as port scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Whitehead et al memorize every observed TCP SYN packet in Bloom filters to detect established TCP connections [20]. Only packets belonging to an established TCP connection are sampled, yet without limiting the number of sampled packets.…”
Section: Related Workmentioning
confidence: 99%
“…Whitehead et al memorize every observed TCP SYN packet in Bloom filters to detect established TCP connections [20]. Only packets belonging to an established TCP connection are sampled, yet without limiting the number of sampled packets.…”
Section: Related Workmentioning
confidence: 99%